How can video recordings best contribute to clinical supervisor training?. (14th October 2016) - Milne, Derek L.
Abstract: Significant progress has been made internationally in the training of clinical supervisors, yet much remains to be done, such as refining training through the improved use of video material. A review of currently available video recordings used in supervisor training indicates that they are generally used informally, are manifestly lacking in procedural detail, are narrowly applied, and lack an educational rationale or research support. After reviewing current options, a more precise, comprehensive and educationally informed framework is proposed, broadening the video options to 10 complementary applications. Systematic links are made between these applications, the core supervision competencies, and the related workshop content (especially training objectives and learning outcomes), culminating in an educational rationale for the use of video within a supervisor training curriculum. It is concluded that application of this framework can enhance the effectiveness and efficiency of supervisor training, helping to maintain progress.